2014
DOI: 10.1007/s00784-014-1192-7
|View full text |Cite
|
Sign up to set email alerts
|

Apical periodontitis and periodontal disease increase serum IL-17 levels in normoglycemic and diabetic rats

Abstract: AP is capable of potentiating systemic inflammatory changes when associated with PD, and increases in blood glucose can accelerate the pathogenesis of oral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 31 publications
6
82
0
2
Order By: Relevance
“…The combination of PL and PD elevated the serum neutrophil levels in diabetic rats (Cintra et al . ). Another study demonstrated that diabetes mellitus upregulated IL‐17 production in PLs and elevated IL‐17 levels in hepatic and renal tissues of rats (Azuma et al .…”
Section: Review Of Identified Publicationsmentioning
confidence: 97%
“…The combination of PL and PD elevated the serum neutrophil levels in diabetic rats (Cintra et al . ). Another study demonstrated that diabetes mellitus upregulated IL‐17 production in PLs and elevated IL‐17 levels in hepatic and renal tissues of rats (Azuma et al .…”
Section: Review Of Identified Publicationsmentioning
confidence: 97%
“…Periodontitis is characterized by inflammation of the periodontal ligament and destruction of alveolar bone . Animal experiments and epidemiological researches confirm that severity of periodontitis is highly related to diabetes . Diabetes could cause complex systemic metabolic change in distant tissues, including periodontal ligament; and levels of inflammatory cytokines were elevated in periodontal tissue of diabetic patients .…”
Section: Introductionmentioning
confidence: 99%
“…Inclui ainda deficiências em combate a infecções, devido a deficiências leucocitárias (26) , e reparos e/ou cicatrizações de processos patológicos, devido à isquemia vascular (6) . Na presente pesquisa, analisou-se, dentro de um banco de dados, a população de pacientes que apresentavam Diabetes Mellitus tipo II, geralmente diagnosticada em indivíduos com mais de 40 anos de idade, de ambos os sexos e obesos (80%).…”
Section: Discussionunclassified